(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article dwells upon the correlative interrelation of communicative approach objectives with prospective teachers’ level of sociocultural competencies. The system of assignments directed at countrystudy competencies formation in the context of prospective specialists’, sociocultural competence has been elaborated.